Meat-eating justification when gender identity is threatened: the association between meat and male masculinity - Mertens, Alica; Oberhoff, Linus (Food quality and preference, 2023)
Identifying psychological barriers that prevent individuals from adopting a meat-free diet is a key to success for environmentalists. The current study experimentally investigates the relation between sex, sex role identification, and meat-eating justification by exposing participants to a gender identity threat or affirmation. In the threat condition, participants received the information that they had below-average levels of masculinity/femininity, whereas in the affirmation group they were told to be above average with regard to their masculinity/femininity. Two-hundred female and 132 male participants were randomly assigned to these conditions. The findings suggest that men and women rationalize their meat consumption differently: While men directly and unapologetically defend their behavior, women tend to avoid recognizing their own responsibility. Moreover, masculinity was associated with direct meat-eating justifications among male, but not among female participants. The experimental manipulation did not affect direct or indirect meat-eating justification. However, further exploratory analyses suggest that how threatening the manipulated feedback was perceived was not primarily dependent on the participant’s sex, but rather the individual identification with sex roles. Therefore, simply basing gender identity threats on participant’s sex might be outdated. The results highlight the association between meat and male masculinity and encourage future studies to take a more nuanced approach to gender identity threats.